Local variation in endoparasite intensities of bank voles (Clethrionomys glareolus )from ecologically similar sites: morphometric and endocrine correlates - Barnard, C.J.; Behnke, J.M.; Bajer, A.; Bray, D.; Race, T.; Frake, K.; Osmond, J.; Dinmore, J.; Sinski, E. (Cambridge University Press, 2002)
Much interest has centred recently on the role of adaptive trade-offs between the immune system and other components of life history in determining resistance and parasite intensities among hosts. Steroid hormones, particularly glucocorticoids and sex steroids, provide a plausible mechanism for mediating such trade-offs. A basic assumption behind the hypothesis, however, is that steroid activity will generally correlate with reduced resistance and thus greater parasite intensities. Here, we present some findings from a field study of bank voles (Clethrionomys glareolus ) in which we have looked at associations between parasite intensities, anatomical and morphometric measures relating to endocrine function and life history variation in three local populations inhabiting similar but mutually isolated woodland habitats. In general, sites with greater parasite intensities were those in which male C. glareolus had significantly larger adrenal glands, testes and seminal vesicles for their age and body size. Females also showed a site difference in adrenal gland weight. Some aspects of site-related parasite intensity were associated with asymmetry in adrenal gland weight and hind foot length, which may have reflected developmental effects on glucocorticoid activity.